BIOETHANOL FROM PINEAPPLE PEEL WITH SACCHAROMYCES CEREVICEAE MASS AND FERMENTATION TIME VARIATION - Nanik Astuti Rahman, Harimbi Setyawati, (Jurnal Teknik Kimia, 2011)
As a waste from pineapple, pineapple peel still contains high carbohydrate and glucose.The aim of this study was to made bioethanol from pineapple peel with variation fromSaccharomyces cereviceae mass addition and fermentation time variation. The variablesused are Saccaromyces cereviceae mass 20, 30, 40 grams, fermentation pH 4 and 5,andthe length of fermentation time 2, 4, 6, 8, and 10 days. The analysis of the obtained resultsshowed: the initial glucose level of pineapple peel extract 8.5325%, the highest levels ofglucose from fermentation was 8.4275%, at the addition of 30 grams Saccaromyces cerevisiae,length of fermentation time was 2 days, and the highest levels of bioethanol was3.965%, it was acquired on the addition of 30 grams Saccaromyces cerevisiae and lengthof fermentation time 10 days. The conclusion of this study is the addition of Saccaromycescerevisiae and the length of fermentation time give a significant effect on the bioetanolproduced from pineapple peel extract.Key words: bioethanol, saccharomyces cereviceae, pineapple peel